Mental disorders in people infected with the coronavirus SARS-CoV-2 – literature review - Litwin, Anna; Masiak, Jolanta (Polish Journal of Public Health, 2020)
In many patients with confirmed or suspected SARS-CoV-2 infection, psychopathological symptoms appeared in connection with the COVID-19 pandemic. The pathogenesis of mental disorders emerging due to the COVID-19 pandemic may include biological and psychosocial factors. COVID-19 can cause symptoms such as insomnia, attention or concentration deficit, anxiety, memory, orientation and consciousness disorders. COVID-19 affects central nervous system functions, which may cause neuropsychological symptoms in some patients, such as dizziness, headaches and consciousness disorders. Psychiatrists must be aware of the side effects of using certain medications among patients with COVID-19. Administration of hydroxychloroquine, an anti-malarial drug, in some hospitalized patients with COVID-19 is associated with occurrence of psychopathological side effects, such as mood and anxiety disorders, insomnia and sometimes psychotic symptoms. The COVID-19 pandemic may adversely impact upon patients with already diagnosed mental disorders. Based on research conducted during present pandemic and past epidemics, it can be assumed that many of these patients will develop: anxiety and depressive disorders, posttraumatic stress disorder (PTSD), substance use disorders. Mental disorders in people infected with the coronavirus SARS-CoV-2 – literature review.